Comparison and classification of an Arctic Transitional snow climate in Tromsø, Norway - Velsand, Paul (UiT Norges arktiske universitet, 2017)
Winter tourism in Tromsø has increased significantly over the last years, consequently also the skiing tourism. It is advertised that Tromsø has a mild coastal climate compared to other destinations at similar latitudes. Existing snow climate classes separate covers into a maritime, continental and a transitional class where persistent weak layers are rare in the maritime class. Rain and average air temperatures during snow season are decisive factors whether a snow pack one single winter is classified as maritime or not (Mock & Birkeland, 2000). In total 76 snow profiles from the winter 2016-2017, in addition to winter meteorological data from 1957 to 2017, have been used to classify the snow cover climate in the Tromsø area. During the winter season 2016–2017, two study plots approximately 25 and 50 km away from open sea were classified as maritime and continental, respectively. Simultaneously, persistent weak layers were observed and forecasted from February to mid-May in both forecasting regions Lyngen and Tromsø. Thus, an Arctic transitional snow climate is defined as having multiple rain-induced crusts in relatively warmer years and extensive depth hoar formation in relatively colder years, where the frequency of constructive metamorphism increase inland. Such a snow cover classification is useful in many ways. Spatial comparison with other areas, both national and international, becomes possible; temporal comparison, making a description of the relation- ship between weak layers and climate, becomes possible; as well as it provides a better data set for Norwegian avalanche forecasters. Also, this thesis provides the Tromsø area with its own snow cover climate describing typical processes influencing snow and snow stability. At best, the knowledge provided may contribute to prevent fatal accidents in snow covered avalanche terrain. Vinterturismen, og også skiturismen, til Tromsøområdet har økt signi- fikant de siste årene. Det blir reklamert med at Tromsø har et mildt kystklima sammenlignet med andre ...